The origins of Walter Rauschenbusch's social ethics - Smucker, Donovan E. (Donovan Ebersole), 1915- (CEL - Canadian Publishers Collection., 1994)
Walter Rauschenbusch is known as the father of the Social Concern movement in America. Traditionally, the source of his social ethic has been seen to lie in the single motif of liberalism. Donovan Smucker provides a new perspective, arguing that Rauschenbusch's social ethic was based on not one but four complementary influences: pietism, sectarianism, liberalism, and transformationism.